Analisis Pengaruh Sense, Feel, Think, Act, dan Relate Terhadap Loyalitas Pengunjung ( Studi Pada Objek Wisata Taman Bunga Selecta Kota Batu ) - Puteri Syarifah Al-Sakinah (Fakultas Ekonomi Universitas Darul Ulum, 2020)
This research is motivated by the formation of loyal customers by touching customer emotions so as to create positive experiences and provide positive feelings towards service products. The purpose of this study was to determine the analysis of the influence of sense, feel, think, act, and relate on partial and simultaneous visitor loyalty as well as the most dominant variable in the Taman Bunga Selecta Tourism Object, Batu City. This study uses a quantitative approach. Sampling was done by means of purposive random sampling of the object under study. The location of this study is more focused on a tourist attraction, namely the Selecta Flower Park in Batu City. Respondents chosen by researchers in this study were visitors to the Selecta Flower Park, Batu City. The regression model test results show that overall sense, feel, think, act, and relate variables have a significant effect on visitor loyalty. Keywords : Sense, Feel, Think, Act, Relate, and Visitor Loyalty